Investigation on Flow and Heat Transfer of Supercritical CO2 in Helical Coiled Tubes at Various Supercritical Pressures - Rao, N. Thiwaan; Oumer, A. N.; Devandran, G.; M. M., Noor (EDP Sciences, 2018)
Supercritical carbon dioxide (scCO2) has unique thermal properties with better flow and heat transfer behavior. However, the flow and heat transfer behavior of scCO2 using helical coil geometries have not fully documented yet. Therefore, the main purpose of this study is to investigate the flow and heat transfer characteristics of scCO2 in helical coiled tubes for heating process using computational fluid dynamics (CFD) method. For the simulation, commercial CFD software called ANSYS FLUENT is used. Helical coiled tube of inner and outer diameter 9.0 mm and 12.0 mm, respectively, with total length of 5500 mm, pitch distance of 32.0 mm and 6 turns of coils is considered. The model is intended to analyze the pressure drops, friction factor, Nusselt number, and goodness factor of scCO2. Three different inlet pressures (8.00 MPa, 9.03 MPa and 10.05 MPa) with three different uniform heat fluxes (20.5 kW/m², 50.5 kW/m² and 80.5 kW/m²) at constant inlet temperature of 27°C are considered. The numerical results are compared with experiment results from previous study to validate the developed model. The wall temperature results from the numerical analysis are in good agreement with the experimental data. From the numerical analysis, the Nusselt number increased significantly when the inlet mass flow rate and heat flux increased. Moreover, it was observed from the simulation results that an increment of average pressure drop by 900 Pa (19.57%) and average friction factor coefficient by 0.1536 (33.85%) when the pressure inlet increased from 9.03 MPa to 10.05 MPa. Hence, the results obtained from this study can provide information for further investigation of scCO2 for industrial applications.